Gentamicin Containing Collagen Implants and Groin Wound Infections in Vascular Surgery: A Prospective Randomised Controlled Multicentre Trial. (April 2020) - Wübbeke, Lina F.; Telgenkamp, Bjorn; van Boxtel, Tiemen; Bolt, Lars J.J.; Houthoofd, Sabrina; Vriens, Patrick W.H.E.; Bouwman, Lee H.; Mees, Barend M.E.; Daemen, Jan Willem H.C.
Abstract : Objective: The aim of this study was to assess the effectiveness of gentamicin containing collagen implants in the reduction of surgical site infections (SSIs) in patients undergoing an inguinal incision for vascular surgery. Methods: Prospective blinded randomised controlled multicentre trial (RCT), performed in four hospitals in The Netherlands and Belgium. This study included 288 patients who underwent an inguinal incision for primary arterial repair (femoral endarterectomy, femorofemoral or femoropopliteal bypass, aortobifemoral bypass, thrombectomy, embolectomy, endovascular aneurysm repair) between October 2012 and December 2015. Patients were randomised to receive a gentamicin implant (study group) or no implant (control group). The calculated sample sizes of 304 patients per group were not reached. Primary outcome was SSI incidence after six weeks. Secondary outcomes were time to onset of infection, length of hospital stay, allergic reactions, treatment with antibiotics, need for re-admission, re-operation and mortality. Results: One hundred fifty-one patients were allocated to the study group (mean age 69 ± 9.2 years) and 137 patients were allocated to the control group (mean age 70 ± 10.4 years). Both groups were homogeneous regarding baseline and intra-operative characteristics. Gentamicin implants did not result in a significant overall reduction of SSIs in the study group (7% vs. 12%, p  = .17). In a post hoc analysis comparing two study sites with low (<10%) and two study sites with high (>10%) infection rates in the control group, gentamicin implants significantly reduced SSIs in high risk centres (22% vs. 1%, p  < .001), whereas there was no significant effect in low risk centres (13% vs . 7%, p  = .30). There were no allergic reactions and all secondary outcomes were comparable between groups. Conclusion: Gentamicin implants did not result in a significant overall reduction of SSIs in this RCT. Gentamicin implants did reduce the incidence of SSIs in high risk centres and may be a valuable adjunct to improve outcomes in such vascular centres with a high incidence of wound infections. However, the limitation of not reaching the calculated sample sizes should be considered.